CAUSES OF RADICALISM BASED ON TERRORISM IN ASPECT OF CRIMINAL LAW POLICY IN INDONESIA - Fitri Wahyuni (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
The phenomenon of radicalism based on terrorism in Indonesia shows a frightening symptom. This can be seen from a number of events that took place in several cities in Indonesia which took action in the name of acts of terror or terrorism such as the 2nd Bali Bombing which killed 22 people and 102 injured. The JW Marriot and Ritz Calton Hotel bombings in 2009 killed nine people and 50 people were injured and the Sarinah Plaza Bomb Jl. MH Thamrin Jakarta on January 14, 2016. With the many actions in the name of terrorism, it is necessary to take steps to anticipate similar actions not being repeated back. This study wants to examine and analyze further about efforts to counter terrorism-based radicalism in Indonesia through criminal law policy. The research method used is normative legal research, namely legal research conducted by examining library materials or secondary legal material while the problem approach is carried out using a legal approach and conceptual approach. The policy in counteracting terrorism in Indonesia is carried out through criminal law policies, namely criminal law policies through means of reasoning and non-reasoning. Penal means in the form of granting criminal sanctions for perpetrators of terrorism with the threat of imprisonment to the most severe threat in the form of capital punishment. But this effort has not provided a deterrent effect for the perpetrators. In criminal law, punishment is not an end in itself and is not the only way to achieve criminal objectives or objectives of the criminal justice system. Therefore another effort is needed which in criminal law is known as a non-reasoning effort.